The Effects of Free‐Living Physical Activity on Mortality After Coronary Artery Disease Diagnosis - Loprinzi, Paul D. (Clin Cardiol, 2016)
BACKGROUND: Previous research demonstrates greater survival among coronary artery disease (CAD) patients who engage in cardiac rehabilitation. No national prospective studies, however, have examined the effects of objectively measured free‐living physical activity on mortality among CAD patients, which is important because only 25% of eligible cardiac patients participate in cardiac rehabilitation. Therefore, the purpose of this study was to examine the association between objectively measured free‐living physical activity on all‐cause mortality among a national sample of CAD patients. HYPOTHESIS: We hypothesize that free‐living physical activity will be inversely associated with all‐cause mortality risk among CAD patients. METHODS: Data from the 2003 to 2006 National Health and Nutrition Examination Survey were used, with follow‐up through 2011. Physical activity was assessed over 7 days during waking hours using the ActiGraph 7164 accelerometer. RESULTS: Among the 256 CAD adults (representative of 6.5 million CAD patients in the United States), 68 died over the follow‐up period (26.56%). The median follow‐up period was 76.5 months (interquartile range = 62–91 months). After adjustment, for every 60‐minute increase in daily free‐living physical activity, CAD patients had a 16% reduced risk of all‐cause mortality (hazard ratio: 0.84, 95% confidence interval: 0.72‐0.97). CONCLUSIONS: Free‐living objectively measured physical activity is associated with greater survival among CAD patients in the United States. If confirmed by future research, development of strategies to not only increase participation in supervised cardiac rehabilitation, but also increase participation in free‐living physical activity, are needed.